ECOLOGIA POPULACIONAL DE Didelphis albiventris LUND, 1840 E Didelphis aurita WIED - NEUWID, 1826 (DIDELPHIDAE, DIDELPHIOMORPHIA) EM FRAGMENTOS DE MATA ATLÂNTICA DE INTERIOR NO ESTADO DO PARANÁ, BRASIL - Valle, Luiz Gustavo Eckhardt (2012)
The study of demographic parameters of animal populations consisted of a conservation strategy based on various factors that influence fluctuating populations such as time, space, resource availability, reproductive patterns, among other variables. The importance of these studies is emphasized when the species of interest have restorative value and /or maintenance of forest structure strategic areas of conservation. Given the scarcity of studies of animal populations on the Plateau of Foz do Iguaçu, outside the area of the National Park of Iguaçu, this study aimed to collect data from two populations of marsupials didelphids at the two major fragments of Biodiversity Corridor Santa Maria (CBSM) and Private Reserve of Natural Heritage Farm Santa Maria (RPPN SM) and São José Farm (FSJ), both in the city of Santa Terezinha de Itaipu, Paraná. Performed six sessions to capture samples of populations. The results showed reproductive concentrated short periods during the rainy season, and the demographic parameters could not point significant differences between species, sex and age classes, this result was relates to the number of sessions, yet even served as useful tools to study the quality areas of CBSM. It was also observed a possible segregation of D. aurita and D. albiventris, which in turn can serve as an indication that the studied areas are not disturbed